"Mystic" transient recurrent nerve palsy after thyroid surgery. Issue 7 (30th July 2012) - Altorjay, Áron; Rüll, Miklós; Paál, Balázs; Csáti, Géza; Szilágyi, Anna
Abstract Background The mechanism of transient recurrent laryngeal nerve (RLN) palsy remains unclear. Methods Samples were harvested from the RLN adjacent thyroid capsule and perineural fascia during 223 lobectomies and 89 RLNs from cadavers were used for histologic and immunohistologic evaluation. Intraoperative chromoendoscopic features of the RLN were compared with postoperative ear, nose, and throat examinations. Results Those nerves that macroscopically seem to be single‐branched (35 of 89 = 39.3%), microscopically consist of multiple fascicles in most of the cases (23 of 35 = 65.7%), resembling a plexus more than a single cord. Chronic lymphocytic infiltration of the thyroid capsule adjacent to the RLN was present in 29% (65 of 223) of the cases. The perineural fascia showed lymphocytic (18 of 223 = 8.1%) or granulocytic (7 of 223 = 3.1%) infiltration. Conclusions The origin of transient RLN palsy is multifactorial: plexus shaped microscopic nerve structure with or without branches, frame‐like adventitial tissue, variable epineurium, inflammatory changes that involve not only the thyroid capsule but the perineural fascia, resultant nerve edema, and diffuse microhemorrhages by injury of fragile capillaries. © 2012 Wiley Periodicals, Inc. Head Neck, 2013